Massive Blood Transfusion in Relation to Delivery: Incidence, Trends, and Risk Factors. Issue 3 (September 2020) - Thurn, L.; Wikman, A.; Westgren, M.; Lindqvist, P.G.
Abstract : ( BJOG . 2019;126:1577–1586) Obstetric hemorrhage is a major contributor to maternal mortality resulting in ∼100, 000 annual deaths worldwide. Massive transfusion may be an indicator of a "near miss event" and is defined as the transfusion of 10 U or more of red blood cells (RBCs) within 24 hours. Recent reports have shown an increase in the rate of massive blood transfusions for postpartum hemorrhage. Yet, the incidence and risk factors of pregnant women requiring massive transfusions is unknown. The aim of this study was to estimate the incidence, trends, and risk factors for massive blood transfusion before and at delivery. In addition, the plasma and RBC transfusion ratio was evaluated as well as the association between massive transfusion and peripartum hysterectomy.